2022
DOI: 10.1029/2022ef002804
|View full text |Cite
|
Sign up to set email alerts
|

Centennial Memory of the Arctic Ocean for Future Arctic Climate Recovery in Response to a Carbon Dioxide Removal

Abstract: Under the ongoing and potential risks from anthropogenic warming, net negative carbon dioxide (CO2) emissions are inevitable to stabilize or recover the Earth's climate. It is important not only to understand climate irreversibility in response to CO2 removal but also to understand how fast each component of the climate system will recover to its original state. Based on idealized CO2 ramp‐up and ‐down ensemble simulations, here we show that the initial buoyancy states of the Arctic Ocean, such as upper ocean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 63 publications
0
13
0
Order By: Relevance
“…Our findings of stronger cold AA may have implications for the effects of various CO 2 removal or net-zero emissions scenarios (Oh et al 2022), instigated by the 2015 Paris Agreement with a pursuit to limit the global temperature increase to 1.5 • C above PI levels, on Arctic climate change. To achieve this objective, net negative CO 2 emissions are demanded (Hoegh-Guldberg et al 2018), so a stronger cold AA signature could emerge.…”
Section: Discussionmentioning
confidence: 74%
“…Our findings of stronger cold AA may have implications for the effects of various CO 2 removal or net-zero emissions scenarios (Oh et al 2022), instigated by the 2015 Paris Agreement with a pursuit to limit the global temperature increase to 1.5 • C above PI levels, on Arctic climate change. To achieve this objective, net negative CO 2 emissions are demanded (Hoegh-Guldberg et al 2018), so a stronger cold AA signature could emerge.…”
Section: Discussionmentioning
confidence: 74%
“…This is mainly due to the slow response time of key Earth system components. Surface air temperature and precipitation changes appear largely reversible at the global scale following a decline in atmospheric CO 2 , but they exhibit irreversibility at regional scale on a timescale of centuries, posing a greater risk to human and natural systems in regions of irreversibility (Kim et al, 2022; Oh et al, 2022). In the long term, irreversible changes include sea-level rise from ocean thermal expansion and melting of ice sheets and glaciers, sea-ice loss, changes in the deep sea environment (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have investigated the reversibility of the climate system, identified hysteresis behavior, and explored associated dynamical processes; the Atlantic Meridional Overturning Circulation (AMOC) [9][10][11] , El Niño-Southern Oscillation 12 , Indian Ocean Dipole 13 , Intertropical Convergence Zone 14 , monsoon 15,16 , carbon uptake 17,18 , drought area 18 , extreme precipitation 19,20 , global heat transport 21 , global mean surface temperature 17,[22][23][24] , and regional precipitation 13,22,23,25 . Among these climate systems, understanding the irreversible and hysteresis behavior of the hydrological cycle is particularly crucial for climate adaptation and mitigation policies, as its changes can have significant impacts on water availability, agriculture, and ecosystems.…”
Section: Mainmentioning
confidence: 99%